Association between Food and Beverage Social Media Exposure with Nutritional Intake of Female Adolescents at SMA Negeri 1 Kota Cirebon, Indonesia - Djamhur, Azwa Dzulafiatul Azizah; Wahidin, Muhammad Duddy Satrianugraha; Fauzah, Shofa Nur (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Background: Previous studies have indicated that exposure to social media can impact adolescents' nutritional intake. Given that 87.5% of Indonesian adolescents use the internet to access social media. Aims: This study aims to analyze how exposure to social media content about food and beverage affect their nutritional intake. Method: The research method used in this study was analytical observational with a cross-sectional approach, involving 114 respondents. Data was collected through a questionnaire of food and beverage social media exposure, anthropometric measurements, and direct interviews using a 24-hour food recall format. Data was analyzed using the Spearman correlation test. Results: Based on the analysis results, it can be concluded that there is a negative relationship between exposure to social media related to food and beverage and adolescent nutritional intake. This means that as exposure to social media content about food and beverage increases, adolescents tend to have lower nutritional intake. The Spearman correlation coefficient of -0.23 supports this finding, indicating a weak but statistically significant negative association. Conclusion: This negative correlation suggests that social media may influence adolescents in ways that may be detrimental to their overall nutritional health. For example, social media platforms often promote foods and beverages that are high in sugar, fat, and calories, which can lead adolescents to make less healthy food choices. In addition, constant exposure to food-related content may create unrealistic expectations about diet and body image, potentially influencing their eating habits. Recommendations for future research focus on the types of food-related content that adolescents encounter, distinguishing between promotional and educational messages, a more diverse sample of adolescents from different schools and socioeconomic backgrounds, and examining confounding variables such as physical activity levels and peer influence. Received: 25 September 2024 | Reviewed: 16 October 2024 | Revised: 30 November 2024 | Accepted: 11 December 2024.